Um estudo sobre as afinações a partir da ontologia fundamental de Martin Heidegger: contribuições para as práticas clínicas - Jardim, Luís Eduardo Franção (2009)
The research s subject is to show Martin Heidegger s concept of humor (Stimmung) in the analytic of Dasein s context, then by the correct comprehension of the concept, come up with an approximation from humors to therapeutic work. We show the basic concepts of analytic of Dasein and the importance humors in this context. The Humors are ways of the disposition, constitutive of Dasein s disclosure, so an ontic concept. We are attuned at all time and our comprehension was already determined by humors. Therapeutic work humors can help comprehension and help the relation between shrink and patient. In the end, an example of being attuned in fear is given from the character Riobaldo of Grande Sertão: Veredas